Improved hospitalization rates in a specialty center for heart failure with preserved ejection fraction and pulmonary hypertension. (7th June 2022) - Kosanovich, Chad M.; Pi, Hongyang; Handen, Adam; Schikowski, Erin; Chen, Yimin; Thoma, Floyd W.; Mulukutla, Suresh; Koscumb, Steve; Nouraie, Mehdi; Chan, Stephen Y.
Abstract: Heart failure with preserved ejection fraction can be complicated by pulmonary hypertension. We designed a retrospective study to provide supporting evidence for referral to specialty care centers. Specialty care centers improved hospitalizations but not mortality—in part due to more aggressive medication management and guideline‐directed monitoring.